Methane and nitrous oxide emissions from dung patches deposited by grazing cattle supplemented with maize grain - Lombardi, Banira (2021)
Feeding management represents an opportunity to improve cattle performance in grazing-based production systems and to mitigate emissions of greenhouse gases (GHG) from livestock production. However, it is unclear how diet affects GHG emissions from dung patches left by grazing cattle. In this study, we evaluated the impact of supplementing the diet of grazing beef steers with maize grain on methane (CH4) and nitrous oxide (N2O) emissions from dung patches, and estimated the corresponding emission factors (EF). Gas fluxes from dung and soil were monitored over 125 days, using the static chamber technique. Dung from supplemented grazing steers produced significantly lower CH4 and higher N2O emissions (1.7 g CH4-C/m2 and 0.4 g N2O-N/m2) than dung from non-supplemented steers (4.0 g CH4-C/m2 and 0.1 g N2O-N/m2). Total GHG emissions from dung showed a tendency to be lower with maize grain supplementation (47.8 and 63.5 ± 5.9 g CO2eq/head/d for supplemented and non-supplemented steers, respectively). The EF values (0.8 g CH4/kg volatile solids (VS) and 0.09 % N2O) were lower than the default values established by IPCC (2006), but comparable to those established by IPCC (2019). Thus, the IPCC (2019) EF values should be used for GHG inventories in the study region (Argentina) until more region-specific values are obtained. Using local data, this study showed that supplementing the diet of grazing steers can reduce dung GHG emissions. Further studies are needed to assess the full implications of dietary supplementation on GHG emissions at farm level.